Persistent bone impairment despite long-term control of hyperprolactinemia and hypogonadism in men and women with prolactinomas - Lukas Andereggen (Nature Portfolio, 2021)
Abstract While prolactinoma patients have high bone turnover, current data are inconclusive when it comes to determining whether correction of hyperprolactinemia and associated hypogandism improves osteodensitometric data in men and women over the long term. In a large cohort of including 40 men and 60 women, we studied the long-term impact of prolactinoma treatment on bone mineral density (BMD) in men versus women, assessed adverse effects of a primary surgical or medical approach, and evaluated data for risk factors for impaired BMD at last follow-up using multivariate regression analyses. Median duration of follow-up was 79 months (range 13–408 months). Our data indicate that the prevalence of impaired BMD remained significantly higher in men (37%) than in women (7%, p < 0.001), despite the fact that hyperprolactinemia and hypogonadism are under control in the majority of men. We found that persistent hyperprolactinemia and male sex were independent risk factors for long-term bone impairment. Currently, osteoporosis prevention and treatment focus primarily on women, yet special attention to bone loss in men with prolactinomas is advised. Bone impairment as “end organ” reflects the full range of the disease and could become a surrogate marker for the severity of long-lasting hyperprolactinemia and associated hypogonadism.